PENGARUH KEPEMIMPINAN, DIKLAT, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PDAM TIRTA MANGUTAMA KABUPATEN BADUNG - Wiratama, I Nyoman Jaka Alit; Sintaasih, Desak Ketut (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 7 Nomor 2 Tahun 2013, 2013)
The purpose of this study was to determine the effect of leadership, education and training, and work discipline on employee performance. The research was conducted at the Regional Water Company Tirta Mangutama Badung regency. Study sample as many as 91 employees, and data analysis techniques of multiple linear regression.  The  results  show  that  leadership,  education  and  training,  and  discipline  of  employees simultaneously significant effect on employee performance. Partially leadership that leadership, education and training, and discipline employees also have a significant effect on employee performance. These results can be interpreted that the presence of direction and good  communication between leaders and subordinates, materials and appropriate training schedule and not disrupt the work activities of employees, as well as a good level of attendance and low work error can improve employee performance
Keywords: leadership, education and training, work discipline, performance